2017
DOI: 10.1136/bmjopen-2017-016690
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children’s context-specific sedentary behaviours and parental socioeconomic status in Finland: a cross-sectional study

Abstract: ObjectivesThis study examined the associations of parental socioeconomic status (SES) with preschoolers’ objectively measured sedentary time (SED) over the course of a week and with parent-reported children’s screen and reading times at home as indicators of sedentary behaviours (SB).DesignCross-sectional.SettingIn years 2015 and 2016 in Finland.Participants864 children, aged 3–6 years, with their parents.Outcome measuresChildren’s accelerometer data were transformed into average SED minutes per hour in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
4
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 63 publications
1
32
4
7
Order By: Relevance
“…A previous study of the DAGIS survey showed no PEL differences in the SED of children (Määttä et al 2017a). This is rather surprising in light of our current study results, since the home environment for children with high PEL seems to be more favourable compared to low PEL families.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A previous study of the DAGIS survey showed no PEL differences in the SED of children (Määttä et al 2017a). This is rather surprising in light of our current study results, since the home environment for children with high PEL seems to be more favourable compared to low PEL families.…”
Section: Discussioncontrasting
confidence: 72%
“…According to Kremers and colleagues (2006), social and physical home environment's associations with EBRBs may vary between population subgroups and sociodemographic factors, including SES. This means that even though no SES differences in children's SED have been found among Finnish preschool children (Matarma et al 2016, Määttä et al 2017a, SES may well in uence the association between home environment and SED. Thus, not only the environmental factors might differ depending on SES, but also the association between factors in home environment and children's SED may differ by SES.…”
Section: Introductionmentioning
confidence: 92%
“…No constant information exists regarding the association between parental educational background and pre-school-aged children’s ST [ 31 ]. Our study also failed to find significant associations between parental educational background and children’s ST [ 53 ]. A better understanding of the potential mechanisms influencing children’s behaviour requires mediational analyses.…”
Section: Discussionmentioning
confidence: 59%
“…Another aspect relevant to examining SES differences is the choice of SES indicator. As shown in our DAGIS study, EBRB differences can be apparent or not, depending on whether the indicator of SES is based on maternal or paternal education [ 52 ]. Additionally, time spent in preschool possibly attenuates SES differences in children’s EBRBs and stress.…”
Section: Discussionmentioning
confidence: 99%